Kesiapan Siswa Sekolah Menengah Kejuruan (Smk) Negeri 3 Sungai Penuh Dalam Melaksanakan Praktek Kerja Industri Didunia Industri - marpeni, meri; rahmiati, rahmiati; izwerni, izwerni (Journal of Home Economics and Tourism, 2013)
This research is descriptive quantitative research, the mainobjective of this study was to reveal about the readiness of studentsof SMK Negeri 3 Full River in implementing the Industrial Practiceindustrialized world. The population in this study amounted to 36people. Samples for the study were taken from the entire population(sampling saturated), all second grade students who are dressmakingindustry practices in the world industry. The data of this studyconsisted of primary data collected directly from respondents withinstruments such as questionnaires (measuring readiness Affectiveand Psychomotor) in the form of questions and tests (cognitivereadiness). From the research shows that the readiness of knowledge(cognitive) are at high category (79.9%), readiness attitudes(affective) that are in the category of very high (88.8%), andreadiness skills (psychomotor) are at high category (79 , 3%). Basedon the descriptive analysis and the results of data classification,grade II readiness fashion SMK 3 full river in implementing theindustrial world pratek industries classified as very high (85.5%)Kata kunci: Kesiapan Pengetahuan (Kognitif), Sikap (Afektif) danKeterampilanÂ  (Psikmotor)